Macroeconomic paradigms and economic policy : from the Great Depression to the Great Recession - Acocella, Nicola, 1939-; Di Bartolomeo, Giovanni, 1969-; Hughes Hallett, Andrew (Cambridge : Cambridge University Press, 2016)
The recent financial crisis has demonstrated the dangers of ignoring the factors that led to previous crises, and the effectiveness of the policies designed to deal with them. Over time, these macroeconomic policies have evolved, oscillating between state intervention and a free-market approach. Following a story that runs from the pre-Great Depression era up until the Financial Crisis of 2007-11, this book reveals an intimate connection between new macroeconomic ideas and policies and the events in the real economy that inspired them. It does this in an accessible, easy-to-follow style, first by focusing on the developments of economic theories and policies, and then by concentrating on the design of domestic and international institutions and economic governance. Written by three leading experts on the history of economic policy, the book is ideal for graduates and undergraduates studying macroeconomics, monetary policy and the history of economic thought.
Machine generated contents note: Preface; Acknowledgements; 1. Introduction; 2. The dawn of the Keynesian Age; 3. The Phillips curve menu; 4. The pro-market counterattack: powerless economic policies; 5. Rethinking stabilization policies: good policies or good luck?; 6. The great recession and beyond; 7. Central banking; 8. Fiscal regimes and fiscal policies; 9. Further policy challenges; 10. Conflicts and cooperation in the labor markets; 11. Fixed exchange rates: the age of tempered liberalism; 12. Free to float: the age of neo-liberalism; 13. A fragile European construction: the perils of incomplete coordination; 14. Taking stock: the end of a ride or the start of a new one?; Bibliography.
Title from publisher's bibliographic system (viewed on 06 Jun 2016).
Keywords: Economic policy -- History; Macroeconomics; Financial crises -- History